Epidemiological, Radiological and Histological Characteristics of Breast Cancer in Patients of a Regional General Hospital in Guerrero, Mexico - Solano Piza, Reyna Isabel; Joanico Morales, Baltazar; Candelario Cruz, Rosalío; Sierra López, Laura; Salgado Jiménez, María de los Ángeles; Rodríguez Echeverría, Gabriela (Atención Familiar, 2021)
Objective: to estimate the frequency and to describe the epidemiological, radiological and histopathological characteristics of women with breast cancer. Methods: cross-sectional study in 2560 women older than 25 years who attended a hospital for a mammography during 2018. The bi-rads classification was described. The clinical records of cancer-positive patients were reviewed and information including epidemiological characteristics, mammography and histopathological study result was collected. The data obtained were analyzed in the Excel program, frequencies and percentages were studied. Results: the frequency of breast cancer was 2.65% (68/2560). 60% were 50 to 69 years of age, 59% were obese and 47% had a family background of breast cancer. According to bi-rads classification, 3% were B3, 45% were B4, 49%, B5 and 3%, B6. Regarding the histopathological report, 83% corresponded to infiltrating ductal carcinoma. Conclusions: in patients with breast cancer, the most frequent characteristics were age from 50 to 69 years, obesity and family background of breast cancer. bi-rads stages 4, 5 and 6 and infiltrating ductal carcinoma were the most frequently described.